A Novel Laminin-Binding Protein Mediates Microbial-Endothelial Cell Interactions and Facilitates Dissemination of Lyme Disease Pathogens. (23rd November 2019) - Bista, Sandhya; Singh, Preeti; Bernard, Quentin; Yang, Xiuli; Hart, Thomas; Lin, Yi-Pin; Kitsou, Chrysoula; Singh Rana, Vipin; Zhang, Fuming; Linhardt, Robert J; Zhnag, Kai; Akins, Darrin R; et al.
Abstract: Borrelia burgdorferi conserved gene products BB0406 and BB0405, members of a common B. burgdorferi paralogous gene family, share 59% similarity. Although both gene products can function as potential porins, only BB0405 is essential for infection. Here we show that, despite sequence homology and coexpression from the same operon, both proteins differ in their membrane localization attributes, antibody accessibility, and immunogenicity in mice. BB0406 is required for spirochete survival in mammalian hosts, particularly for the disseminated infection in distant organs. We identified that BB0406 interacts with laminin, one of the major constituents of the vascular basement membrane, and facilitates spirochete transmigration across host endothelial cell barriers. A better understanding of how B. burgdorferi transmigrates through dermal and tissue vascular barriers and establishes disseminated infections will contribute to the development of novel therapeutics to combat early infection. Abstract : We discovered that a Borrelia burgdorferi protein, BB0406, is required for pathogen survival in mammalian hosts, particularly for the disseminated infection in distant organs. We identified that BB0406 interacts with laminin and facilitates microbial transmigration across host endothelial cell barriers.